Measurement of B + c production in proton-proton collisions at √s=8 TeV - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; et al. (Physical review letters, 2015)
Production of B+c mesons in proton-proton collisions at a center-of-mass energy of 8 TeV is studied with data corresponding to an integrated luminosity of 2.0 fb−1 recorded by the LHCb experiment. The ratio of production cross sections times branching fractions between the B+c→J/ψπ+ and B+→J/ψK+ decays is measured as a function of transverse momentum and rapidity in the regions 0<pT<20 GeV/c and 2.0<y<4.5. The ratio in this kinematic range is measured to be (0.683±0.018±0.009)%, where the first uncertainty is statistical and the second systematic.